2010
DOI: 10.1089/jop.2009.0077
|View full text |Cite
|
Sign up to set email alerts
|

Topical Piperacillin/Tazobactam for Recalcitrant Pseudomonas Aeruginosa Keratitis

Abstract: Therapy-resistant P. aeruginosa keratitis acquired from the community is becoming an increasing problem. Topical piperacillin/tazobactam is an option for the treatment of therapy-resistant P. aeruginosa keratitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Topical or intraocular piperacillin/tazobactam has been used for the treatment of such cases. [ 34 35 ]…”
Section: Discussionmentioning
confidence: 99%
“…Topical or intraocular piperacillin/tazobactam has been used for the treatment of such cases. [ 34 35 ]…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] It is not uncommon to come across multidrug resistant P. aeruginosa isolates, especially in patients with keratitis and endophthalmitis. [17,18] Topical or intraocular piperacilin/tazobactum have been used for the treatment of such cases. [17,18] Fewer studies have reported the level of antibiotic resistance among Enterobacteriaceae isolated from eye infections.…”
Section: Antimicrobial Resistancementioning
confidence: 99%
“…[17,18] Topical or intraocular piperacilin/tazobactum have been used for the treatment of such cases. [17,18] Fewer studies have reported the level of antibiotic resistance among Enterobacteriaceae isolated from eye infections. In one study, the resistance to gatifloxacin was 3.4%, to ofloxacin and ciprofloxacin was 5.1% and to gentamicin was 8.5%.…”
Section: Antimicrobial Resistancementioning
confidence: 99%
“…18 Sometimes a combination of piperacillin/tazobactam might be effective with unresponsive P. aeruginosa MK. 52 …”
Section: Introductionmentioning
confidence: 99%